The Response of Sensitive LULC Changes to Runoff and Sediment Yield in a Semihumid Urban Watershed of the Upper Awash Subbasin Using the SWAT+ Model, Oromia, Ethiopia - Bekan Chelkeba Tumsa (Applied and Environmental Soil Science)
Land use and land cover (LULC) changes in many parts of river basins have caused water shortages, flood risks, land degradation, soil loss, biodiversity loss, and ecosystem deterioration. LULC change and topography are the main factors that cause land degradation and soil erosion in the Ethiopian highlands. The aim was to evaluate the rate of the LULC change and its effects on runoff and sediment yield in the semihumid subtropical Awash watershed using the SWAT + model. The land use maps of 2000, 2010, and 2020, along with constant climate data from 1992 to 2020, were used to investigate the effects of LULC dynamics on runoff and sediment yields. Agriculture and urbanization both increased at 7.1% and 7.95%, respectively. In contrast, the forest area decreased by 8.8% and shrubland by 3.25% from 2000 to 2020. Bare soil and urban areas covered the majority of the landscape units that were labeled as potential runoff generators. The majority of the soil erosion-prone areas that were classified as severe in the second and third scenarios covered a sizable area of urban, agricultural, and shrubland. These soil erosion hotspots covered an area of 3,777.3 ha (3.18%) and 13,413.1 ha (11.3%), with a total annual sediment yield of 361.93 m/ton and 1239.24 m/ton, respectively. In general, the change in LULC results in the annual sediment yield, with mean annual amounts of 241.8 tons/ha, 408.7 tons/ha, and 732.4 tons/ha for each scenario in the sequence. The model performance was tested using R2 = 0.88, NSE = 0.9, and PBIAS = −2.36, which indicate good agreement between simulated and observed flow, and R2 = 0.82, NSE = 0.86, and PBIAS = 4.38 for the simulated against recorded sediment yield. The increases in sediment yields have serious implications for reservoir siltation downstream of the watershed and warn land use managers to take action.